The role of urinary VEGF in BPS/IC observational studies: A systematic review - Aurora Maria Barreto Gomes da Costa (2022)
Background: Bladder pain syndrome/Interstitial cystitis (BPS/IC) is a chronic pain condition, often underdiagnosed, with an important impact on patient quality of life. More recently, it has been suggested an association between VEGF and its receptors in BPS/IC pathophysiology, due to their role in promoting angiogenesis and inflammation, which can enhance bladder pain. Eventually, VEGF may be used as a biomarker for the diagnosis and prognostication of BPS/IC. To further clarify this issue this review aims at critically summarizing the available information, giving rise to a solid starting point for future studies. Methods: We systematically searched PubMed and Scopus, using the queries "urinary VEGF", "urinary VEGF" AND "pain", "urinary VEGF" AND "lower urinary tract symptoms" and "urinary VEGF" AND "LUTS" from January 2016 to February 2022. Results: A total of 1026 papers were identified from which 7 articles were included in this study which assessed 1036 participants. Regarding VEGF levels, overactive bladder (OAB) and healthy patients were used for comparison with BPS/IC patients. VEGF concentration seems to be higher when compared to healthy patients and overactive bladder (OAB) patients. Higher levels of VEGF were associated with pain severity, while a decrease in VEGF concentration is associated with pain and symptom improvement in women. However, these findings were not constant in all studies. Conclusions: There is a trend towards a relevant association between increased VEGF levels and pain or symptom severity in BPS/IC patients. Although there are some discrepancies among the studies and the number of patients included is a small, VEGF and its receptors should be considered for future studies regarding its use in BPS/IC pathophysiology, diagnosis and prognostication.